The influence of emotional intelligence towards employee job performance among employees at Talent Corporation Malaysia / Puteri Nur Syaheraa Surani - Surani, Puteri Nur Syaheraa (Faculty of Business and Management, 2019)
Employee job performance has always been a major challenge in every organization. Employers need to ensure employees can achieve and deliver higher job performance because it is believed as instrumental to organization’s growth and profitability. Recently, emotional intelligence has been a central attention of researchers as it can influence employee job performance. Therefore, the purpose of this study was to identify the influences of emotional intelligence towards employee job performance as well as to identify the most influential factor of emotional intelligence elements towards employee job performance among employees at Talent Corp Malaysia. This study used convenience sampling technique and online questionnaire as an instrument to collect data. The data from 78% of 110 employees were collected then evaluated by using Statistical Package for the Social Science (SPSS) Version 22 Software. The result from Multiple Regression analysis indicated self-awareness and motivation have significant relationship with employee job performance while self-management has no significant relationship with employee job performance. Moreover, it has revealed that motivation is most influential variables towards employee job performance among employees at Talent Corp Malaysia.